The Interplay of the Unfolded Protein Response in Neurodegenerative Diseases: A Therapeutic Role of Curcumin - Mukherjee, Sitabja; Mishra, Awdhesh Kumar; Peer, G. D. Ghouse; Bagabir, Sali Abubaker; Haque, Shafiul; Pandey, Ramendra Pati; Raj, V. Samuel; Jain, Neeraj; Pandey, Atul; Kar, Santosh Kumar (Frontiers in Aging Neuroscience, 2021)
Abnormal accumulation of misfolded proteins in the endoplasmic reticulum and their aggregation causes inflammation and endoplasmic reticulum stress. This promotes accumulation of toxic proteins in the body tissues especially brain leading to manifestation of neurodegenerative diseases. The studies suggest that deregulation of proteostasis, particularly aberrant unfolded protein response (UPR) signaling, may be a common morbific process in the development of neurodegeneration. Curcumin, the mixture of low molecular weight polyphenolic compounds from turmeric, Curcuma longa has shown promising response to prevents many diseases including current global severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and neurodegenerative disorders. The UPR which correlates positively with neurodegenerative disorders were found affected by curcumin. In this review, we examine the evidence from many model systems illustrating how curcumin interacts with UPR and slows down the development of various neurodegenerative disorders (ND), e.g., Alzheimer’s and Parkinson’s diseases. The recent global increase in ND patients indicates that researchers and practitioners will need to develop a new pharmacological drug or treatment to manage and cure these neurodegenerative diseases.